Agitational and Propagandistic Measures to Activate Cossack Volunteer Movement in Don Region during Great Patriotic War - V. A. Bondarev (Научный диалог)
This study addresses the enhancement of agitational and propagandistic measures to activate Cossack volunteerism in the Don region during the Great Patriotic War. Various sources, including archival and published documents, periodicals, testimonies, and contemporaries’ memoirs, were utilized. A comparative-historical analysis of agitational and propagandistic activities conducted in the Don region from 1941 to 1945 indicates significant changes in Soviet approaches and methods of agitation during wartime. Initially, internationalism and socio-political motives (class-based approach) dominated Soviet propaganda at the war’s outset, akin to the pre-war period, leading to the primary involvement of communists, Komsomol members, and Civil War veterans in the Cossack volunteer movement. However, pre-war propaganda approaches quickly lost their effectiveness. By autumn 1941, national-patriotic motives took precedence in Soviet agitation and propaganda efforts. In the Don region, these changes manifested in propaganda appealing to the illustrious combat history of the Don Cossacks and exalting regional patriotism. It is demonstrated that adjusting agitational and propagandistic measures towards strengthening national-patriotic motives proved highly effective, ensuring a steady influx of volunteers into Cossack cavalry formations.